Scaffolding Academic Writing through Genre-Based Instruction: A Holistic Insight into Students’ Skills, Collaboration, Metacognitive Awareness, and Motivation - Samsudin Samsudin; Asbar Asbar; Sukarismanti Sukarismanti (STAI Hubbulwathan Duri, 2025)
Academic writing poses significant challenges for English as a Foreign Language (EFL) students, particularly in resource-limited contexts. Genre-Based Instruction (GBI), grounded in Systemic Functional Linguistics, offers structured scaffolding that may enhance students' cognitive, metacognitive, and affective engagement in writing. This qualitative multi-case study explored the holistic impact of GBI on high school students' academic writing, collaboration, metacognitive awareness, and motivation. Data were collected from 321 students across two schools in Enrekang Regency, Indonesia. Twelve students (representing active and passive learners) were purposively selected for semi-structured interviews, complemented by classroom observations and reflective journals. Data were analyzed thematically using Braun and Clarke’s framework with Atlas.ti software. The findings revealed that GBI significantly improved students’ academic writing skills, particularly in organizing ideas, understanding rhetorical structures, and using appropriate language features. Students reported enhanced metacognitive awareness, such as planning, monitoring, and evaluating their writing. Collaborative learning fostered deeper conceptual understanding, peer feedback, and reflective thinking. Furthermore, GBI reduced writing anxiety and increased students’ confidence and motivation by providing clear scaffolds and explicit textual models. This study demonstrates that GBI can serve as a transformative pedagogy that addresses not only linguistic competence but also students’ emotional and cognitive needs. It provides practical implications for teachers and curriculum developers aiming to promote inclusive, reflective, and structured academic literacy in EFL classrooms, especially in under-resourced educational settings.